Impact of Lepidopteran Oral Secretions on the Transcriptome of Arabidopsis thaliana - Angel Fernandez Martin; Philippe Reymond (Plant Direct)
ABSTRACT Plants respond to attack by chewing insects through the recognition of herbivore‐associated molecular patterns (HAMPs) that are present in oral secretions (OS) and released at the wound site, leading to appropriate deployment of plant immune responses. Because insect feeding is accompanied by severe wounding of the leaf tissue, the specific contribution of HAMPs to defense is not well characterized. Also, OS contain effectors that interfere with the activation of defenses, but the underlying downregulated genes are poorly studied. Here, we analyzed the transcriptome of Arabidopsis thaliana leaves in response to wounding alone or to wounding and application of OS from Spodoptera littoralis or Pieris brassicae. For both insects, OS amplified wound‐induced responses and specifically promoted the activation of stress and hormonal pathways, as well as pathogen‐related responses. In contrast, OS inhibited the expression of genes involved in the regulation and biosynthesis of aliphatic glucosinolates (GS), and cell wall strengthening. In addition, OS‐mediated suppression of wound‐induced ERF114 and wound healing‐related genes uncovered a novel strategy to impair defenses. In support of these findings, we observed an increased performance of S. littoralis and P. brassicae larvae feeding on OS‐treated Arabidopsis plants. Altogether, we highlight a major contribution of OS components to plant response to herbivory and unveil the potential role of conserved OS‐derived effector(s) in inhibiting defenses.